Public interests : media advocacy and struggles over U.S. television - Perlman, Allison, 1975- (Rutgers University Press, 2016)
Public Interests fills in a key part of the history of American social reform movements, revealing the impressive battles fought by groups like the NAACP, NOW, and the conservative Parents Television Council to shape both the nation's television programming and its broadcasting policies. Allison Perlman takes us behind the scenes of several key regulatory fights, in the process vividly illustrating the resilience, flexibility, and diversity of media activist campaigns from the 1950s onward.